A Study on Socio-Economic Background of Entrepreneurs in Small Scale Industries - Jagapathi Rao, G. V. (Indian Journal of Marketing, 2010)
The small scale industrial (SSI) sector has been considered as a powerful instrument for achieving "Accelerated Industrial Growth" and creating "Productive Employment Opportunities" in an economy. This sector also plays two important roles as producers of consumer goods and absorbers of surplus labour, thereby addressing the agents that help in mitigating regional imbalances, facilitate mobilization of local resources and skills, which might have otherwise remained unutilized. In recent years, the SSI sector has emerged as a dynamic and vibrant sector of the Indian economy, displaying its phenomenal growth in the varied fields of production, employment and dispersed development, in general and exports in particular.